The Influence of Problem Based Learning and Student Teams Achievement Divisions on Student Achievement - Arina Mustaanah (Jurnal Ad'ministrare, 2022)
The purpose of this study was to find out how the application of the Problem Based Learning and Study Team Achievement Desicion learning model affects the learning achievement of 5th grade elementary school students in thematic learning. The research method uses a quasi-experimental or quasi-experimental method with the research design of Nonequivalent Control Group Design. In this study, researchers used two groups, namely the experimental 1 group which is treated with the Problem Based Learning model and the experimental 2 group which is required by the Student Team Achievement Divisions learning model. The sample was determined by total sampling, which means that the entire population became the research sample, namely the 5th grade students of SDN Purworejo, totaling 19 students and SDN Dersansari 02, totaling 22 students, meaning that the total sample was 41 students. Data collection tools using normative tests and data analysis using normality test, homogeneity test, and hypothesis testing. The results of the study in terms of the results of the different test (t) determine the experimental 1 class of 75.79 and the experimental 2 class of 84.09. Meanwhile, the results of the N-Gain test showed that the experimental 1 class was 39.9% and the experimental 2 class was 60.3%, so it can be concluded that improving student learning achievement is more effective when using the STAD model.